Effect of the Fukushima earthquake on weight in early childhood: a retrospective analysis. Issue 1 (7th February 2018) - Ono, Atsushi; Isojima, Tsuyoshi; Yokoya, Susumu; Kato, Noriko; Tanaka, Toshiaki; Yamagata, Zentaro; Chida, Shoichi; Matsubara, Hiroko; Tanaka, Soichiro; Ishikuro, Mami; Kikuya, Masahiro; Kuriyama, Shinichi; et al.
Abstract : Objective: There have been no reports evaluating the physical growth in early childhood in Fukushima Prefecture after the Great East Japan Earthquake. We retrospectively investigated the health examination data in early childhood (aged 0–3 years). Methods: We divided the affected children into respective groups according to the interval from the disaster to the time of health examination and age as follows: group I, birth to 3–4 months in boys (1.81 (range, 0–6 months)) and girls (1.79 (range, 0–7 months)); group II, 3–4 months to 6–10 months in boys (6.37 (range, 3–9 months)) and girls (6.35 (range, 3–9 months)); group III, 6–10 months and 18 months in boys (16.2 (range, 5–22 months)) and girls (16.9 (range, 5–22 months)); and group IV, 18 months to 36–42 months in boys (21.0 (range, 18–24 months)) and girls (21.0 (range, 18–24 months)). Using height and body mass index, the health status of each group was compared with that of unaffected controls (ie, children who experienced the disaster after their health examination at 36–42 months). Results: The change in body mass index between the health examinations at 18 months and 36–42 months was significantly increased in group I (95% CI: all boys, 0.192 to 0.276 vs −0.006 to 0.062, P<0.001 and all girls, 0.108 to 0.184 vs −0.109 to −0.035, P<0.001) and group II (95% CI: all boys, 0.071 to 0.141 vs −0.006 to 0.062, P=0.002 and all girls, −0.042 to 0.024 vs −0.109 to −0.035, P=0.013). Conclusions: Children who were affected by the disaster in Fukushima Prefecture in early childhood were overweight. The use of pre-existing information, such as health examination data, was beneficial for investigating the physical growth of affected children.